2017
DOI: 10.1016/j.clinbiochem.2016.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of thyroid function in intensive care unit patients by liquid chromatography tandem mass spectrometry methods

Abstract: Objectives Patients with non-thyroidal illness syndrome have many abnormalities in thyroid hormone tests. Such patients have medical comorbidities associated with low serum proteins and are on multiple medications that interfere with thyroid hormone measurement by immunoassay platforms. It is unknown if these thyroid hormone measurements reflect physiologic conditions or if they are artifacts of testing methodology. Methods Fifty patients were selected from the intensive care unit (ICU) from our institution.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…However, various practical and technical issues related to above-mentioned challenges of TH physiology and pathophysiology hampered rapid progress and success in quantification of total and free THM concentrations. While meanwhile several laboratories developed procedures to accurately determine total T4 and total T3 in human plasma or serum and largely agree on concentrations ranges (25,(67)(68)(69)(70)(71)(72)(73), this consensus has not been achieved yet for most of the other TH metabolites, which occur at much lower concentrations. Analytical procedures typically work well with buffer solutions, in vitro reaction mixtures, as well as with samples of "simple" matrix composition, while reported concentrations in human or experimental animal serum, plasma, and tissue show wide variations and marked insufficiencies in terms of method validation, standardization, and quality assessment parameters [see (23,24,74)].…”
Section: Alternative Lc-ms-based Approaches Are Needed To Determine Cmentioning
confidence: 99%
“…However, various practical and technical issues related to above-mentioned challenges of TH physiology and pathophysiology hampered rapid progress and success in quantification of total and free THM concentrations. While meanwhile several laboratories developed procedures to accurately determine total T4 and total T3 in human plasma or serum and largely agree on concentrations ranges (25,(67)(68)(69)(70)(71)(72)(73), this consensus has not been achieved yet for most of the other TH metabolites, which occur at much lower concentrations. Analytical procedures typically work well with buffer solutions, in vitro reaction mixtures, as well as with samples of "simple" matrix composition, while reported concentrations in human or experimental animal serum, plasma, and tissue show wide variations and marked insufficiencies in terms of method validation, standardization, and quality assessment parameters [see (23,24,74)].…”
Section: Alternative Lc-ms-based Approaches Are Needed To Determine Cmentioning
confidence: 99%
“…The developed method reduces the run time from 14 to 5 min and as an isocratic method it removes the need for column re-equilibration in between samples. The method also shows improvements over those previously published in terms of precision, extraction recoveries and correlation [ 32 35 ]. Tanoue et al [ 35 ] reported extraction recoveries, for low concentration, 82.9, 81.9, 83.5 and 62.7% and for high concentration, 86.9, 90.5, 90.0 and 69.6% for T4, T3, rT3 and T2, respectively.…”
Section: Resultsmentioning
confidence: 74%
“…There are a number of papers documenting the development and comparison of LC-MS methods for the analysis of thyroid hormones, utilising positive ionisation. These include the thyroid hormones T4 and/or T3 [ 32 34 ] as well as rT3 and T2 [ 35 ]. Typical sample preparation extraction recoveries, for the thyroid hormones, ranged between 62.7 and 114% with a coefficient of variation of 1.8–31% and precision between 3.8 and 12% [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possibility is that our method for FT4, which is equilibrium dialysis-tandem mass spectrometry, has been found to be less affected by the metabolic changes of acute illness, including low-binding proteins, than older immunoassay methods for measuring FT4. 9 Another potential cause of low FT4 with nonelevated TSH is hypopituitarism, and thyroid testing is appropriate when there is clinical suspicion of that diagnosis, such as detection of an ectopic posterior pituitary on MRI. Although testing for possible hypopituitarism was done in 29 children, no cases of low FT4 due to a new diagnosis of hypopituitarism were identified.…”
Section: Discussionmentioning
confidence: 99%